2022
DOI: 10.3788/col202220.040602
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and stable coupling of kilowatt-level continuous wave laser into hollow-core fibers

Abstract: Fiber gas lasers based on gas-filled hollow-core fibers (HCFs) perfectly combine the advantages of fiber lasers and gas lasers and have obtained fast development in the past years. However, stable and efficient coupling of high-power pump lasers into the HCFs is one of the key problems to be solved. In this paper, we study the coupling of high-power continuous wave fiber lasers into anti-resonant HCFs through an end-cap. By optimizing the splicing parameters, a maximum laser power of 1167 W was injected into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Their latest research demonstrated an efficiency of 90.4% and the CW delivery of 50 W with a stable and alignment-free all-fiber laser setup [378]. The newest result reported by Cui et al obtained a highly efficient and stable launching into AR-HCF with the maximum transmission power reaching 1021 W through splicing the AR-HCF with a fiber endcap [382], the experimental setup can be found in Fig. 7e.…”
Section: Breakthrough Of Microstructure Fibers For High-power Deliverymentioning
confidence: 91%
See 3 more Smart Citations
“…Their latest research demonstrated an efficiency of 90.4% and the CW delivery of 50 W with a stable and alignment-free all-fiber laser setup [378]. The newest result reported by Cui et al obtained a highly efficient and stable launching into AR-HCF with the maximum transmission power reaching 1021 W through splicing the AR-HCF with a fiber endcap [382], the experimental setup can be found in Fig. 7e.…”
Section: Breakthrough Of Microstructure Fibers For High-power Deliverymentioning
confidence: 91%
“…AR-HCF is one of the most popular microstructure fibers according to the emerging results reported recently. High-power pulse delivery employing AR-HCFs has been a well-known topic, it appears that researchers are turning more and more attention to its CW delivery applications [371][372][373][374][375][376][377][378][379][380][381][382][383].…”
Section: Breakthrough Of Microstructure Fibers For High-power Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the fabrication between the HCF and end-cap can be found in Refs. [25, 26]. The other end is fixed in the gas cell, which can be used to fill the HC-PCF with H 2 .…”
Section: Methodsmentioning
confidence: 99%